Diaphragm and preparation method thereof, battery and electric equipment
By coating antiperovskite materials and organic solid electrolytes on the base film of the lithium-ion battery separator, the problem of the separator shrinkage at high temperature and insufficient ion transmission capacity of the ceramic coating is solved, and the fast charging and rate performance of the battery is improved.
Patent Information
- Application Number
- CN202411994772.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
The existing lithium-ion battery separators have shrinkage problems at high temperatures, and the ion transmission capacity of the ceramic coating is insufficient, which affects the battery's fast charging and magnification capabilities.
Antiperovskite material and organic solid electrolyte are coated on the base film to form a multi-layer structural membrane. Antiperovskite materials are used to inhibit separator shrinkage, while organic solid electrolytes improve ion transport capabilities.
It effectively suppresses the heat shrinkage of the diaphragm, improves the ion transmission capability of the battery, and enhances the fast charging and rate performance of the battery.
Smart Images

Figure CN119905780A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a diaphragm and a preparation method thereof, a battery and an electrical device. Background Art
[0002] As environmental problems become increasingly severe, new energy technologies have received widespread attention. As one of the important new energy sources, the safety and endurance of lithium-ion batteries are the research and development focuses. As a safety guarantee for lithium-ion batteries, lithium battery separators play an important role. Their role is to block electrons, mechanically separate the positive and negative electrodes, and prevent internal short circuits in the battery. At the same time, the microporous structure of the separator provides a channel for lithium ions to transfer between the positive and negative electrodes, ensuring the normal progress of the electrochemical reaction.
[0003] The mainstream diaphragm base film currently used is polypropylene PP or polyethylene PE coated diaphragm. PP uses dry diaphragm, and its expansion resistance is better than PE, but the PP film is thicker, which is not conducive to improving the energy density of the battery cell. The heat resistance and expansion resistance of the PE film are poor. It is thinner but needs to be coated with ceramics, which can increase the heat resistance and expansion performance of the diaphragm. The coated ceramic alumina itself does not have the ability to transmit ions, and will block pores, reducing the diffusion channel of lithium ions, thereby inhibiting fast charging and reducing the rate capacity. In addition, the coated ceramic itself has weak adhesion and is easy to fall off. Therefore, in business, glue is often further applied to the base film coated with ceramic. The glue is generally PVDF to increase the direct adhesion between the diaphragm and the electrode and shorten the lithium ion diffusion path, but the lithium ion conductivity is poor. Therefore, the diaphragm technology needs to be further improved. Summary of the invention
[0004] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application proposes a diaphragm with high shrinkage resistance or ion transmission capacity and a preparation method thereof, a battery and an electrical device.
[0005] In a first aspect, the present application proposes a diaphragm, comprising: a base film and a functional coating, wherein the functional coating comprises a first coating and a second coating, wherein the first coating is disposed on at least one side of the base film, and the second coating is disposed on a side of the first coating away from the base film; the first coating comprises an antiperovskite material, and the second coating comprises an organic solid electrolyte. Thus, the diaphragm of the present application has a high ion transmission capacity while having good resistance to thermal shrinkage.
[0006] In some embodiments, the antiperovskite material includes Li3OF, Li3OCl, Li3OBr, Li3OI, Li3OCl 0.5 Br 0.5 , Li3OBH4, Li3SBF4, Li3S(BF4) 0.5 Cl0.5 At least one of the above. This can improve the ion transmission capacity, while not reacting in the operating temperature range of the lithium battery, and can effectively inhibit the shrinkage of the diaphragm.
[0007] In some embodiments, the surface density of the first coating is 0.1 mg / cm 2 ~10mg / cm 2 The surface density of the second coating is 0.1 mg / cm 2 ~100mg / cm 2 This helps to increase the energy density of the battery.
[0008] In some embodiments, the base film includes at least one of polypropylene, polyethylene, non-woven fabric, and polyethylene terephthalate. Thus, the material source is wide and the cost is low.
[0009] In some embodiments, the base film has a thickness of 4 μm to 20 μm, which is beneficial to improving the energy density of the battery cell.
[0010] In some embodiments, the organic solid electrolyte includes at least one of polyethylene oxide, polymethyl methacrylate, and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0011] The second aspect of the present application provides a method for preparing a diaphragm, comprising:
[0012] Coating a slurry containing an antiperovskite material on at least one surface of the base film to form a first coating;
[0013] dissolving the high molecular weight organic matter in a first organic solvent to obtain a first solution;
[0014] Dissolving a polymer graft modified substance, a lithium salt, a plasticizer and a photoinitiator in a second organic solvent to obtain a second solution, and initiating polymerization of the polymer graft modified substance to obtain a third solution;
[0015] The first solution, the third solution and the thermal initiator are mixed and coated on the surface of the first coating layer away from the base film, so that the high molecular organic matter and the polymerized high molecular graft modified substance undergo cross-linking reaction to form a second coating layer, thereby obtaining the diaphragm.
[0016] The present application can effectively inhibit the shrinkage of the diaphragm and improve the ion transmission capacity of the diaphragm by coating the antiperovskite material and the organic solid electrolyte on the surface of the base film.
[0017] In some embodiments, before preparing the slurry, the process further includes: grinding the antiperovskite material into particles with a size of 0.1 μm to 20 μm, thereby improving the dispersibility of the antiperovskite material and making the first coating more uniform.
[0018] In some embodiments, the high molecular organic matter includes at least one of polyethylene oxide, polymethyl methacrylate, and polyvinylidene fluoride-hexafluoropropylene copolymer. Thus, the material source is wide and the cost is low.
[0019] In some embodiments, the polymer graft includes at least one of oligomers of acrylate and its derivatives and crosslinked products of small molecule additives; the small molecule additive includes at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile. Thus, the material source is wide and the cost is low.
[0020] In some embodiments, the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. As a result, the material source is wide and the cost is low, which is conducive to improving the ion transmission capacity of the diaphragm.
[0021] In some embodiments, the plasticizer includes at least one of a carbonate compound, an ether compound, and a sulfone compound. Thus, the material source is wide, the cost is low, and it is beneficial to improve the toughness of the diaphragm.
[0022] In some embodiments, the concentration of the polymer grafted modified substance in the second solution is 10 mg / mL to 200 mg / mL, which is beneficial to increase the reaction rate and reduce the waste of raw materials.
[0023] In some embodiments, the temperature of the cross-linking reaction is 60° C. to 200° C., and the pressure is 0.1 MPa to 2 MPa, which is beneficial to increase the cross-linking rate and save reaction time.
[0024] The third aspect of the present application provides a battery, comprising the diaphragm described in the first aspect of the present application or the diaphragm prepared by the method described in the second aspect of the present application, thereby improving the fast charging capability of the battery.
[0025] The fourth aspect of the present application provides an electrical device, comprising the battery described in the third aspect of the present application. The electrical device has all the features and advantages of the battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the diaphragm in Example 1 of the present application.
[0027] Figure 2 It is a schematic diagram of the diaphragm in Example 3 of the present application.
[0028] Figure 3 It is a schematic diagram of the diaphragm in Example 7 of the present application.
[0029] Figure 4 It is a schematic diagram of the diaphragm in Example 4 of the present application.
[0030] Figure 5 It is a schematic diagram of the diaphragm in Example 6 of the present application.
[0031] Figure 6 It is a schematic diagram of the diaphragm in comparative example 3 of the present application.
[0032] Figure 7 It is a schematic diagram of the diaphragm in comparative example 4 of the present application.
[0033] Reference numerals:
[0034] 1- second coating layer, 2- first coating layer, 3- base film, 4- alumina layer, 5- PVDF layer. DETAILED DESCRIPTION
[0035] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0036] In the first aspect of the present application, a diaphragm is proposed, comprising: a base film and a functional coating, wherein the functional coating comprises a first coating and a second coating, wherein the first coating is arranged on at least one side of the base film, and the second coating is arranged on a side of the first coating away from the base film; the first coating comprises an antiperovskite material, and the second coating comprises an organic solid electrolyte. The first coating of the diaphragm described in the present application is an antiperovskite material coating, which can effectively inhibit the shrinkage of the diaphragm and greatly improve the ion transmission capacity; the second coating is an organic solid electrolyte coating, which, on the one hand, replaces PVDF to play a bonding role, and on the other hand, the polymer is a solid electrolyte layer, which makes up for the reduction of the ion transmission path caused by the pore blocking of the coating, thereby indirectly improving the ion transmission capacity of the diaphragm.
[0037] It should be noted that the diaphragm described in the present application needs to have both an antiperovskite material coating and an organic solid electrolyte coating. The antiperovskite material can be set on one side or both sides, and the organic solid electrolyte can also be set on one side or both sides, which can be flexibly selected according to specific needs. When one side of the base film is an antiperovskite material and an organic solid electrolyte, the antiperovskite material needs to be set close to the base film. As an example, the setting methods of the diaphragm include but are not limited to the following:
[0038] (1) Both the antiperovskite material and the organic solid electrolyte are set on both sides. For details, please refer to Figure 1 ;
[0039] (2) The antiperovskite material is set on one side, and the organic solid electrolyte is set on both sides. For details, please refer to Figure 2;
[0040] (3) Antiperovskite material is set on both sides, and organic solid electrolyte is set on one side. For details, please refer to Figure 3 ;
[0041] (4) The antiperovskite material and the organic solid electrolyte are both set on one side. The antiperovskite material and the organic solid electrolyte are on the same side. For details, please refer to Figure 4 ;
[0042] (5) The antiperovskite material and the organic solid electrolyte are both set on one side, and the antiperovskite material and the organic solid electrolyte are on different sides. For details, please refer to Figure 5 .
[0043] In some embodiments, the antiperovskite material includes Li3OF, Li3OCl, Li3OBr, Li3OI, Li3OCl 0.5 Br 0.5 , Li3OBH4, Li3SBF4, Li3S(BF4) 0.5 Cl 0.5 Among them, the antiperovskite material has a greatly improved ion transmission capacity compared with the alumina ceramic layer, and at the same time does not react within the operating temperature range of the lithium battery, has the ability to be soft and non-shrinking, and can effectively inhibit the shrinkage of the diaphragm.
[0044] In some embodiments, the surface density of the first coating is 0.1 mg / cm 2 ~10mg / cm 2 (e.g. 0.1 mg / cm 2 , 0.5mg / cm 2 , 1mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 or 10mg / cm 2 The surface density of the second coating is 0.1 mg / cm 2 ~100mg / cm 2 (e.g. 0.1 mg / cm 2 , 0.5mg / cm 2 , 1mg / cm 2 , 5mg / cm 2 、10mg / cm 2 , 20mg / cm 2、30mg / cm 2 , 40mg / cm 2 、50mg / cm 2 、60mg / cm 2 、70mg / cm 2 、80mg / cm 2 、90mg / cm 2 or 100mg / cm 2 The surface density refers to the mass per unit area, and the calculation formula is: surface density = mass / area. When the surface density is within the above range, it is beneficial to improve the energy density of the battery.
[0045] In some embodiments, the base film includes at least one of polypropylene (PP), polyethylene (PE), non-woven fabric, and polyethylene terephthalate. Thus, the material source is wide and the cost is low.
[0046] In some embodiments, the base film has a thickness of 4 μm to 20 μm, for example, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm, etc. This is beneficial to improving the energy density of the battery cell.
[0047] In some embodiments, the organic solid electrolyte includes at least one of polyethylene oxide, polymethyl methacrylate, and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0048] The second aspect of the present application provides a method for preparing a diaphragm, comprising:
[0049] S1: coating a slurry containing an antiperovskite material on at least one surface of a base film to form a first coating layer.
[0050] In some embodiments, before preparing the slurry, the process further includes: grinding the antiperovskite material into particles with a size of 0.1 μm to 20 μm (such as 0.1 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm, etc.), which is beneficial to improve the dispersibility of the antiperovskite material and make the first coating more uniform. The ground particles can then be dispersed in an NMP solvent, a dispersant is added, and the mixture is evenly mixed and then coated on the surface of the base film to form the first coating.
[0051] S2: dissolving the high molecular weight organic matter in a first organic solvent to obtain a first solution.
[0052] In some embodiments, the high molecular organic matter includes at least one of polyethylene oxide (PEO), polymethyl methacrylate (PMMA), and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP). Therefore, the material source is wide and the cost is low.
[0053] Specifically, the high molecular organic matter can be dissolved in NMP solvent and stirred evenly to form a first solution.
[0054] S3: dissolving the polymer graft modified product, lithium salt, plasticizer and photoinitiator in a second organic solvent to obtain a second solution, and initiating polymerization of the polymer graft modified product to obtain a third solution.
[0055] Specifically, the lithium salt can be first dissolved in the organic solvent NMP and stirred evenly, then the oligomers of acrylate and its derivatives are added and dissolved, and then the plasticizer, small molecule additive and photoinitiator are added and stirred evenly to form a second solution, and the second solution is irradiated with ultraviolet light to initiate polymerization to form a third solution.
[0056] In some embodiments, the polymer graft includes at least one of oligomers of acrylate and its derivatives and crosslinked products of small molecule additives; the small molecule additive includes at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile. Thus, the material source is wide and the cost is low.
[0057] In some embodiments, the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. As a result, the material source is wide and the cost is low, which is conducive to improving the ion transmission capacity of the diaphragm.
[0058] In some embodiments, the plasticizer includes at least one of a carbonate compound, an ether compound, and a sulfone compound. Thus, the material source is wide, the cost is low, and it is beneficial to improve the toughness of the diaphragm.
[0059] In some embodiments, the concentration of the polymer grafted modified substance in the second solution is 10 mg / mL to 200 mg / mL, for example, 10 mg / mL, 20 mg / mL, 50 mg / mL, 80 mg / mL, 100 mg / mL, 120 mg / mL, 150 mg / mL, 180 mg / mL or 200 mg / mL, etc. This is beneficial to increase the reaction rate and reduce the waste of raw materials.
[0060] S4: Mix the first solution, the third solution and the thermal initiator and apply them on the surface of the first coating layer away from the base film, so that the high molecular organic matter and the polymerized high molecular grafted modified substance undergo cross-linking reaction to form a second coating layer, thereby obtaining the diaphragm.
[0061] Specifically, the uniformly dissolved first solution can be added to the third solution irradiated with ultraviolet light to form a uniform solution, and a thermal initiator is added. After being stirred evenly, the solution is coated on the surface of the anti-perovskite base film to perform a thermal crosslinking reaction.
[0062] In some embodiments, the temperature of the cross-linking reaction is 60°C to 200°C, for example, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, etc., and the pressure is 0.1MPa to 2MPa, for example, 0.1MPa, 0.2MPa, 0.4MPa, 0.6MPa, 0.8MPa, 1MPa, 1.2MPa, 1.4MPa, 1.6MPa, 1.8MPa or 2MPa, etc. This is conducive to improving the cross-linking rate and saving reaction time.
[0063] The third aspect of the present application provides a battery, comprising the diaphragm described in the first aspect of the present application or the diaphragm prepared by the method described in the second aspect of the present application, thereby improving the fast charging capability of the battery.
[0064] It can be understood that there is no special restriction on the specific type of the battery, which can be a primary battery or a secondary battery; the shape of the battery can be a cylindrical battery, a square battery or a battery of any other shape, etc.; classified by the outer packaging, the battery can be a hard shell battery, a soft pack battery, etc.
[0065] Typically, in addition to the diaphragm described in the present application, the battery also includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet, the negative electrode sheet and the diaphragm can be made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte can be contained in an outer package. During the battery charging and discharging process, the active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through.
[0066] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a conductive agent and a binder, and the positive electrode current collector may include a metal foil, for example, the metal foil may be an aluminum foil. The positive electrode active material may include lithium nickel cobalt manganese oxide (NCM811), lithium nickel cobalt manganese oxide (613), lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based materials or positive electrode active materials commonly used in the art. The conductive agent may include acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.
[0067] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent and a binder, wherein the negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, a silicon-containing carbon-based composite material, a lithium-containing metal composite material, a lithium metal material and a common negative electrode active material in the art. The thickener may be a thickener sodium carboxymethyl cellulose (CMC-Na) and a conventional material in the art. The conductive agent may be acetylene black and a conventional material in the art. The binder may be styrene-butadiene rubber and a conventional material in the art.
[0068] The fourth aspect of the present application provides an electrical device, comprising the battery described in the third aspect of the present application. The electrical device has all the features and advantages of the battery described above, which will not be described one by one here.
[0069] In some embodiments, the battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0070] The embodiments of the present application are described in detail below.
[0071] Example 1
[0072] (1) The antiperovskite material Li3OCl was ground into particles of 10 μm in size, dispersed in NMP solvent, added with a dispersant, mixed evenly, and coated on both sides of a 5 μm thick PE base film to form a first coating with a coating surface density of 0.6 mg / cm 2 ;
[0073] (2) dissolving polyethylene oxide (PEO) in NMP organic solvent and stirring evenly to form solution A with a solid content of 30%;
[0074] (3) dissolving LiPF6 in an organic solvent of NMP and stirring evenly, then adding and dissolving oligomers of acrylates and their derivatives, and then adding carbonate compounds, small molecule additives malononitrile and photoinitiator and stirring evenly to form a solution B; the concentration of oligomers of acrylates and their derivatives in solution B is 100 mg / mL;
[0075] (4) Add the uniformly dissolved solution A to the ultraviolet-irradiated solution B to form a uniform solution, add a thermal initiator, stir evenly and coat it on both sides of the antiperovskite base film, with a coating surface density of 1 mg / cm 2 , a cross-linking reaction is carried out, the temperature of the cross-linking reaction is 100° C., and the pressure is 1 MPa, to form a second coating, the first coating and the second coating are both double-sided coating and on the same side;
[0076] (5) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0077] Example 2
[0078] (1) The antiperovskite material Li3OCl was ground into particles of 10 μm in size, dispersed in NMP solvent, added with a dispersant, mixed evenly, and coated on both sides of a 12 μm thick PP base film to form a first coating with a coating surface density of 0.6 mg / cm 2 ;
[0079] (2) dissolving polyethylene oxide (PEO) in NMP organic solvent and stirring evenly to form solution A with a solid content of 30%;
[0080] (3) dissolving LiPF6 in an organic solvent of NMP and stirring evenly, then adding and dissolving oligomers of acrylates and their derivatives, and then adding carbonate compounds, small molecule additives malononitrile and photoinitiator and stirring evenly to form a solution B; the concentration of oligomers of acrylates and their derivatives in solution B is 100 mg / mL;
[0081] (4) Add the uniformly dissolved solution A to the ultraviolet-irradiated solution B to form a uniform solution, add a thermal initiator, stir evenly and coat it on both sides of the antiperovskite base film, with a coating surface density of 1 mg / cm 2 , a cross-linking reaction is carried out, the temperature of the cross-linking reaction is 100° C., and the pressure is 1 MPa, to form a second coating, the first coating and the second coating are both double-sided coating and on the same side;
[0082] (5) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0083] Example 3
[0084] (1) The antiperovskite material Li3OBr was ground into particles of 0.1 μm in size, dispersed in NMP solvent, added with a dispersant, mixed evenly, and coated on one side of a 5 μm thick PE base film to form a first coating with a coating surface density of 0.8 mg / cm 2 ;
[0085] (2) dissolving polymethyl methacrylate (PMMA) in NMP organic solvent and stirring evenly to form solution A with a solid content of 10%;
[0086] (3) dissolving LiBF4 in an organic solvent of NMP and stirring evenly, then adding and dissolving oligomers of acrylates and their derivatives, and then adding ether compounds, small molecule additives succinonitrile and photoinitiators and stirring evenly to form a solution B; the concentration of oligomers of acrylates and their derivatives in solution B is 10 mg / mL;
[0087] (4) Add the uniformly dissolved solution A to the ultraviolet-irradiated solution B to form a uniform solution, add a thermal initiator, stir evenly and coat it on both sides of the antiperovskite base film, with a coating surface density of 1.5 mg / cm 2 , a cross-linking reaction is carried out, the temperature of the cross-linking reaction is 60° C., and the pressure is 0.1 MPa, to form a second coating, the second coating is double-sided coating, and the first coating and the second coating are on the same side;
[0088] (5) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0089] Example 4
[0090] (1) The antiperovskite material Li3OBr was ground into particles of 20 μm in size, dispersed in NMP solvent, added with a dispersant, mixed evenly, and coated on one side of a 5 μm thick PE base film to form a first coating with a coating surface density of 0.8 mg / cm 2 ;
[0091] (2) dissolving polyethylene oxide (PEO) in NMP organic solvent and stirring evenly to form solution A with a solid content of 60%;
[0092] (3) dissolving LiAsF6 in an organic solvent of NMP and stirring evenly, then adding and dissolving oligomers of acrylates and their derivatives, and then adding sulfone compounds, small molecule additives malononitrile and photoinitiator and stirring evenly to form a solution B; the concentration of oligomers of acrylates and their derivatives in solution B is 200 mg / mL;
[0093] (4) Add the uniformly dissolved solution A to the ultraviolet-irradiated solution B to form a uniform solution, add a thermal initiator, stir evenly and coat it on one side of the antiperovskite base film, with a coating surface density of 1.5 mg / cm 2 , a cross-linking reaction is carried out, the temperature of the cross-linking reaction is 200° C., and the pressure is 2 MPa, to form a second coating, wherein both the first coating and the second coating are coated on one side and on the same side;
[0094] (5) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0095] Example 5
[0096] (1) Antiperovskite material Li3OCl 0.5 Br 0.5 The particles were ground into 20 μm particles, dispersed in NMP solvent, and dispersant was added. After mixing evenly, the particles were coated on one side of a 5 μm thick PE base film to form the first coating. The coating surface density was 0.4 mg / cm 2 ;
[0097] (2) dissolving polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP in NMP organic solvent and stirring evenly to form solution A with a solid content of 60%;
[0098] (3) dissolving LiCF3SO3 in an organic solvent of NMP and stirring evenly, then adding and dissolving oligomers of acrylates and their derivatives, and then adding sulfone compounds, small molecule additives malononitrile and photoinitiator and stirring evenly to form a solution B; the concentration of oligomers of acrylates and their derivatives in solution B is 200 mg / mL;
[0099] (4) Add the uniformly dissolved solution A to the ultraviolet-irradiated solution B to form a uniform solution, add a thermal initiator, stir evenly and coat it on both sides of the antiperovskite base film, with a coating surface density of 0.5 mg / cm 2 , a cross-linking reaction is carried out, the temperature of the cross-linking reaction is 200° C., and the pressure is 2 MPa, to form a second coating, wherein the first coating and the second coating are on the same side;
[0100] (5) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0101] Example 6
[0102] (1) Antiperovskite material Li3OCl 0.5 Br 0.5 The particles were ground into 20 μm particles, dispersed in NMP solvent, and dispersant was added. After mixing evenly, the particles were coated on one side of a 5 μm thick PE base film to form the first coating. The coating surface density was 0.4 mg / cm 2 ;
[0103] (2) dissolving polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP in NMP organic solvent and stirring evenly to form solution A with a solid content of 60%;
[0104] (3) dissolving LiCF3SO3 in an organic solvent of NMP and stirring evenly, then adding and dissolving oligomers of acrylates and their derivatives, and then adding sulfone compounds, small molecule additives malononitrile and photoinitiator and stirring evenly to form a solution B; the concentration of oligomers of acrylates and their derivatives in solution B is 200 mg / mL;
[0105] (4) Add the uniformly dissolved solution A to the ultraviolet-irradiated solution B to form a uniform solution, add a thermal initiator, stir evenly and coat it on both sides of the antiperovskite base film, with a coating surface density of 0.5 mg / cm 2 , a cross-linking reaction is carried out, the temperature of the cross-linking reaction is 200° C., and the pressure is 2 MPa, to form a second coating, wherein the first coating and the second coating are on opposite sides;
[0106] (5) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0107] Example 7
[0108] (1) Antiperovskite material Li3OCl 0.5 Br 0.5 Grind into 20 μm particles, disperse in NMP solvent, add dispersant, mix evenly and coat on both sides of 5 μm thick PE base film to form the first coating with a coating surface density of 0.4 mg / cm 2 ;
[0109] (2) dissolving polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP in NMP organic solvent and stirring evenly to form solution A with a solid content of 60%;
[0110] (3) dissolving LiCF3SO3 in an organic solvent of NMP and stirring evenly, then adding and dissolving oligomers of acrylates and their derivatives, and then adding sulfone compounds, small molecule additives malononitrile and photoinitiator and stirring evenly to form a solution B; the concentration of oligomers of acrylates and their derivatives in solution B is 200 mg / mL;
[0111] (4) Add the uniformly dissolved solution A to the ultraviolet-irradiated solution B to form a uniform solution, add a thermal initiator, stir evenly and coat it on one side of the antiperovskite base film, with a coating surface density of 0.5 mg / cm 2 , a cross-linking reaction is carried out, the temperature of the cross-linking reaction is 200° C., and the pressure is 2 MPa, to form a second coating, wherein the first coating and the second coating are on the same side;
[0112] (5) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0113] Comparative Example 1
[0114] A 5 μm thick PP separator was assembled into a battery with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte.
[0115] Comparative Example 2
[0116] A 5 μm thick PE separator was assembled into a battery with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte.
[0117] Comparative Example 3
[0118] (1) Alumina is dispersed in NMP solvent, a dispersant is added, the mixture is evenly mixed, and then coated on both sides of a 5 μm thick PE base film;
[0119] (2) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0120] Comparative Example 4
[0121] (1) PVDF glue was coated on both sides of a 5 μm thick PE base film;
[0122] (2) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0123] Comparative Example 5
[0124] (1) Alumina was dispersed in NMP solvent, a dispersant was added, the mixture was evenly mixed, and then coated on one side of a 5 μm thick PE base film;
[0125] (2) coating PVDF glue on the alumina layer;
[0126] (3) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0127] Comparative Example 6
[0128] (1) Alumina was dispersed in NMP solvent, a dispersant was added, the mixture was evenly mixed, and then coated on one side of a 5 μm thick PE base film;
[0129] (2) coating the PVDF glue on the other side of the PE base film;
[0130] (3) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0131] Comparative Example 7
[0132] (1) Alumina is dispersed in NMP solvent, a dispersant is added, the mixture is evenly mixed, and then coated on both sides of a 5 μm thick PE base film;
[0133] (2) coating PVDF glue on both sides of the PE base film;
[0134] (3) Assemble the prepared diaphragm with a positive electrode sheet coated with lithium iron phosphate, a graphite negative electrode sheet, and a carbonate electrolyte to form a battery.
[0135] The experimental conditions are shown in Table 1.
[0136] Table 1 Experimental conditions
[0137]
[0138] The above examples and comparative examples were tested in the following manner:
[0139] 1. Diaphragm porosity: take an area of 100cm 2 Prepare the base film S, and record the weight as m1 by weighing. According to the theoretical density of the base film ρ and the thickness of the diaphragm h, the theoretical diaphragm weight m2 = ρ × S × h can be calculated, and then the diaphragm porosity ε = (1-m1 / m2) × 100%
[0140] 2. Membrane air permeability: Use a cutting knife to cut three membranes of 100 mm × membrane width from the membrane roll at 150 mm intervals in the longitudinal direction. Place the membranes in a permeability tester for air permeability test. Record the area of 6.45 cm2 for 100 mL of air passing under a pressure of 1.21 kPa. 2 The time taken for the diaphragm.
[0141] 3.10μL diffusion rate in electrolyte: Use a 10μL pipette to draw electrolyte drops onto the surface of the prepared diaphragm, and use a stopwatch to record the time when there are no obvious droplets on the diaphragm surface.
[0142] 4. Adhesion ability between the diaphragm and the negative electrode sheet: After the diaphragm and the positive and negative electrode sheets are stacked into a battery, they are hot-pressed at 90°C, 3min, and 3000kgf. After hot-pressing, the diaphragm and the negative electrode sheet are peeled off a certain distance and placed on a tensile testing machine for a peeling force test.
[0143] 4. Heat shrinkage: Use a cutting knife to cut the diaphragm into at least 5 pieces of 100mm×100mm standard samples. The side length of the standard sample must be parallel or perpendicular to the TD direction of the diaphragm. After cutting, mark the TD or MD direction, and then select the 3 flattest samples from the 5 samples as the samples to be tested. Then use a marker and a steel ruler to mark the range of 80mm×80mm, recorded as T0 and M0; take the upper and lower layers of uncontaminated printing paper and nail them into a paper fixture, put the paper fixture loaded with the sample into a constant temperature drying oven that has reached 130℃, start timing for 1h, after the heating is completed, wait for the sample to cool to room temperature, use an imager with a film ruler to measure the length marked with TD and MD, recorded as T and M, and the shrinkage rate MD and shrinkage rate TD are calculated according to the following formulas:
[0144] 6. Battery rate performance: At 25°C, first charge to 3.65V at 0.2C constant current and constant voltage, then discharge to 2.0V at 0.2C. After 5 minutes of standing, charge to 3.65V at 3C constant current and constant voltage, then discharge to 2.0V at 0.2C. The battery rate performance can be calculated by calculating the 3C constant current charging capacity / 0.2C constant current charging capacity.
[0145] 7. Battery three-electrode fast charging capability: The battery cells are stacked in the order of the first diaphragm, the negative electrode sheet, the first diaphragm, and the positive electrode sheet. Before the last set of negative and positive electrode sheets are stacked, the first end of the reference electrode is sanded with sandpaper to remove the oxide layer and then loaded into the battery cell, and the reference electrode inserted into the battery cell is covered with the second diaphragm so that the reference electrode inserted into the battery cell is placed between the first diaphragm and the second diaphragm. A nickel strip is welded to the second end of the reference electrode as the reference electrode tab, and the positive and negative tabs of the battery cell are welded. After the battery cell is assembled, liquid is injected and packaged; the battery is charged at different rates, and the lithium plating potential of the negative electrode is monitored through the reference electrode. When the negative electrode potential is consistent with the reference electrode potential, it means that the fast charging capability of the battery cell is at this level, otherwise the charging current at the rate is continued to increase.
[0146] The test results of the embodiments and comparative examples are shown in Table 2 below:
[0147] Table 2 Test results
[0148]
[0149] It can be seen from the test results of Examples 1 to 7 and Comparative Examples 1 to 7 that the coating of the inorganic anti-perovskite layer and the organic solid electrolyte layer in the present application can significantly increase the ion diffusion rate and compensate for the loss of fast charging capacity caused by pore blockage.
[0150] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0151] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0152] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A diaphragm, characterized in that: include: A base film and a functional coating, wherein the functional coating comprises a first coating and a second coating, wherein the first coating is arranged on at least one side of the base film, and the second coating is arranged on a side of the first coating away from the base film; the first coating comprises an antiperovskite material, and the second coating comprises an organic solid electrolyte.
2. The diaphragm according to claim 1, characterized in that The antiperovskite material includes Li3OF, Li3OCl, Li3OBr, Li3OI, Li3OCl 0.5 Br 0.5 , Li3OBH4, Li3SBF4, Li3S(BF4) 0.5 Cl 0.5 At least one of .
3. The diaphragm according to claim 1, characterized in that The surface density of the first coating is 0.1 mg / cm 2 ~10mg / cm 2 ; and / or The surface density of the second coating is 0.1 mg / cm 2 ~100mg / cm 2 .
4. The diaphragm according to claim 1, characterized in that The base film comprises at least one of polypropylene, polyethylene, non-woven fabric, and polyethylene terephthalate; and / or The base film has a thickness of 4 μm to 20 μm.
5. The diaphragm according to claim 1, characterized in that The organic solid electrolyte includes at least one of polyethylene oxide, polymethyl methacrylate, and polyvinylidene fluoride-hexafluoropropylene copolymer.
6. A method for preparing the diaphragm according to any one of claims 1 to 5, characterized in that: include: Coating a slurry containing an antiperovskite material on at least one surface of the base film to form a first coating; dissolving the high molecular weight organic matter in a first organic solvent to obtain a first solution; Dissolving a polymer graft modified substance, a lithium salt, a plasticizer and a photoinitiator in a second organic solvent to obtain a second solution, and initiating polymerization of the polymer graft modified substance to obtain a third solution; The first solution, the third solution and the thermal initiator are mixed and coated on the surface of the first coating layer away from the base film, so that the high molecular organic matter and the polymerized high molecular graft modified substance undergo cross-linking reaction to form a second coating layer, thereby obtaining the diaphragm.
7. The method according to claim 6, characterized in that Before preparing the slurry, the method further includes: grinding the antiperovskite material into particles with a size of 0.1 μm to 20 μm.
8. The method according to claim 6, characterized in that The macromolecular organic substance comprises at least one of polyethylene oxide, polymethyl methacrylate, and polyvinylidene fluoride-hexafluoropropylene copolymer; and / or The polymer graft comprises at least one of oligomers of acrylate and its derivatives and crosslinked products of small molecule additives; and / or The lithium salt comprises at least one of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2; and / or The plasticizer includes at least one of a carbonate compound, an ether compound, and a sulfone compound.
9. The diaphragm according to claim 8, characterized in that The small molecule additive includes at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid and sebacononitrile.
10. The method according to claim 6, characterized in that The concentration of the polymer grafted modified substance in the second solution is 10 mg / mL to 200 mg / mL.
11. The method according to claim 6, characterized in that The temperature of the cross-linking reaction is 60° C. to 200° C., and the pressure is 0.1 MPa to 2 MPa.
12. A battery, characterized in that: The invention comprises the diaphragm according to any one of claims 1 to 5 or the diaphragm prepared by the method according to any one of claims 6 to 11.
13. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 12.
Citation Information
Cited By
Composite diaphragm, preparation method thereof and battery
CN121076412A